Hierarki Birokrasi dalam Sistem Anggaran Digital: Studi Implementasi Inovasi E-Budgeting pada Pemerintah Kota Surabaya - Astried Pamella Cholifah; Bintoro Wardiyanto; Erna Setijaningrum (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Currently, bureaucracy is under scrutiny due to the increasing use of social media and the increasing political literacy of young people and the general public. Bureaucratic reform provides a strong foundation for managing regional government. This reform effort encourages the formation of a professional and efficient public administration system, where changes can occur starting from the institutional structure and work culture. The focus of this research is how the budget implementation has shifted to using electronic technology. Does it still use a clear hierarchy of authority to the national government or the city of Surabaya, which fully controls this application? This research uses a descriptive qualitative approach that aims to understand and describe the implementation of e-Budgeting Innovation in the Surabaya City Government. The results of this study indicate that the bureaucratic hierarchy in the digital budget system essentially still follows the existing government organizational structure, but the process has become more efficient, transparent, and automated through the use of digital technology. In Surabaya, e-budgeting has been running for quite some time, and the bureaucratic hierarchy is already functioning well. Digitalization tends to reduce slow procedures and high transaction costs, rather than eliminating the hierarchy itself. Overall, the implementation of e-Budgeting in Surabaya is a successful example of financial governance. With the development of the times, the application of ICT systems in various parts of public life has also developed..